2009
DOI: 10.1093/gerona/glp046
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Increase in Cytokine Production During Systemic Inflammation: Adipose Tissue as a Major Source of IL-6

Abstract: Increased mortality and overexpression of interleukin-6 (IL-6) during inflammatory stress are well-documented age-associated phenomena; however, the site of IL-6 overexpression is not entirely known. Here, we report that white adipose tissue is a major source of IL-6 in aged animals during lipopolysaccharide (LPS)-induced systemic inflammation. Among the various tissues examined, white adipose tissue from the epididymal fat pad (located in the abdominal cavity) expressed the highest level of IL-6 messenger RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 36 publications
3
121
0
1
Order By: Relevance
“…We observed that 10 wk of treatment with INCB18424 did not alter number of peripheral blood immune cells in aged mice (Table S3). Adipose tissue is a major source of the cytokines in aged animals (44,45). We found that the expression of several inflammatory markers and matrix metalloproteinases in adipose tissue, including IL-6, TNF-α, MMP-3, MMP-12, and EGF-like module-containing mucin-like hormone receptor-like 1 (Emr1 or F4/80), a macrophage marker, was decreased in the INCB18424-treated group, (Fig.…”
Section: Inhibition Of Jak/stat Pathways Decreases Systemic and Adiposementioning
confidence: 76%
See 1 more Smart Citation
“…We observed that 10 wk of treatment with INCB18424 did not alter number of peripheral blood immune cells in aged mice (Table S3). Adipose tissue is a major source of the cytokines in aged animals (44,45). We found that the expression of several inflammatory markers and matrix metalloproteinases in adipose tissue, including IL-6, TNF-α, MMP-3, MMP-12, and EGF-like module-containing mucin-like hormone receptor-like 1 (Emr1 or F4/80), a macrophage marker, was decreased in the INCB18424-treated group, (Fig.…”
Section: Inhibition Of Jak/stat Pathways Decreases Systemic and Adiposementioning
confidence: 76%
“…In this study, we mainly used human primary preadipocytes to study cellular senescence and the SASP because fat tissue is a major source of circulating inflammatory cytokines in aged populations (44,45) and because fat tissue is the largest organ in most humans and preadipocytes thus are perhaps the most abundant progenitor cell type in humans (39). It is likely that senescent cells in other tissues contribute to age-related inflammation as well.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of ageing varies across species and is genetically based (Bowen and Atwood 2004). In humans, the ageing phenotype is characterized by hearing loss, visual impairment (Roth 2015), wrinkles and other skin conditions (Yosipovitch et al 2007), a steady decline in many cognitive processes (Deary et al 2009), a decrease in sex and growth hormones (Masternak and Bartke 2012), and increased inflammation (Starr et al 2009). The elderly are the fastest-growing segment of the population, and it is estimated that by 2050, there will be two billion people over the age 60 and they will outnumber the children (Glatt et al 2007).…”
Section: Ageingmentioning
confidence: 99%
“…Furthermore, it has been shown that caloric restriction in old animals reduces the levels of pro-inflammatory cytokines to levels comparable to those of young animals (Spaulding et al 1997). Chronically elevated levels of pro-inflammatory markers, such as interleukin 6 (IL-6) or tumor necrosis factor-α (TNF-α), are key features of ageing since low-grade inflammatory activity in the elderly is common (Starr et al 2009;Bruunsgaard et al 2001). This pro-inflammatory environment has been defined as Binflammaging.^TNF-α and IL-6 have become frailty markers of ageing in humans (Hernandez-Bautista et al 2014); however, the mechanisms that cause and preserve high levels of these markers in ageing are poorly understood.…”
Section: Inflammation and Ageing Inflammagingmentioning
confidence: 99%
See 1 more Smart Citation